Influence of Various Adhesives on Properties of Betung Bamboo Laminated Boards - Rudi Hartono; Unedo Liberti Carlos Simbolon; Tito Sucipto; Evalina Herwati; Jajang Sutiawan; Aprilia Kartikawati; Riska Surya Ningrum; Teguh Darmawan; Ihak Sumardi; Muhammad Navis Rofii; Trisna Priadi (BioResources)
Bamboo can be engineered for laminate boards and other sustainable construction material. The adhesive type is expected to affect the laminated board's quality. This study analyzed the physical (density, moisture content, and delamination) and mechanical (bending and shear strength) properties of betung (Dendrocalamus asper) bamboo laminated boards prepared using various adhesives. The most favorable adhesive for enhancing betung bamboo laminated boards was determined. The bamboo lamina was arranged into boards (3 layers) measuring 30 x 15 x 1.5 cm each in length, width, and thickness. The laminated board was glued using isocyanate, epoxy, and polyvinyl acetate (PVAc) adhesives using the double glue spread technique. The laminated board was tested for its physical and mechanical properties, following the JAS 234:2003 standard. Betung bamboo laminated board with isocyanate, epoxy, and PVAc adhesives had densities ranging from 0.89 g/cm3 to 0.95 g/cm3, moisture contents of 7.64% to 24.37%, delamination ranges from 0% to 100%, modulus of elasticities from 109,000 to 178,000 kg/cm2, modulus of rupture values ​​range from 709 to 1,570 kg/cm2, and shear strength values ​​of 25.0 to 60.0 kg/cm2. Isocyanate adhesive was found to have the best quality in physical tests, while epoxy adhesive achieved the best quality in mechanical tests of laminated boards.